2007
DOI: 10.1111/j.1365-3083.2007.01978.x
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Serodiagnosis of Mycobacterium tuberculosis Infection

Abstract: One‐third of the world population is estimated to have Mycobacterium tuberculosis infection. Accurate and timely identification of infected individuals is critical for treatment and control. The current diagnostic methods lack the desired sensitivity and specificity, require sophisticated equipment and skilled workforce or take weeks to yield results. Diagnosis of extrapulmonary TB, TB‐HIV co‐infection, childhood TB and sputum smear‐negative pulmonary TB pose serious challenges. Interest in developing serodiag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
121
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(122 citation statements)
references
References 126 publications
(174 reference statements)
0
121
0
1
Order By: Relevance
“…With regard to the onset of the immune response, methylation of HBHA appears to be crucial for the induction of T-cell antigenicity and protective immunity against M. tuberculosis (Temmerman et al, 2004). Methylated HBHA may thus be a suitable diagnostic marker for identifying individuals with active TB (Abebe et al, 2007).…”
Section: Adhesins As Serodiagnostic Markers For M Tuberculosismentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to the onset of the immune response, methylation of HBHA appears to be crucial for the induction of T-cell antigenicity and protective immunity against M. tuberculosis (Temmerman et al, 2004). Methylated HBHA may thus be a suitable diagnostic marker for identifying individuals with active TB (Abebe et al, 2007).…”
Section: Adhesins As Serodiagnostic Markers For M Tuberculosismentioning
confidence: 99%
“…Several M. tuberculosis antigenic proteins have been evaluated as serological markers, particularly culture filtrate proteins, although surface-exposed proteins appear to be more effective (Abebe et al, 2007).…”
Section: Adhesins As Serodiagnostic Markers For M Tuberculosismentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid, inexpensive diagnostic tests would aid these countries in limiting the spread of infection within their communities (WHO 2009). In addition, molecular methods based on nucleic acid amplification to diagnose TB infection are rapid, highly specific and more sensitive than microscopic examination of smears, but are less sensitive compared to culture assays for smear-negative TB cases (Abebe et al 2007).Serological tests that rely on the detection of antibodies against Mycobacterium tuberculosis-specific antigens possess several advantages: they are simple, inexpensive and feasible for the diagnosis of TB. Potential M. tuberculosis antigens were recently reviewed in a metaanalysis.…”
mentioning
confidence: 99%
“…These results indicated that highly specific tests frequently exhibited poor sensitivity, which limited the use of these antigens when a single antigen was used in the assay (Steingart et al 2009). Recently, there has been renewed interest in the development of antibody-based diagnostic assays that utilise multiple antigens to achieve high sensitivity and specificity (Abebe et al 2007). Many attempts to develop a serologic TB test have been made.…”
mentioning
confidence: 99%